Java 9 regular expressions : zero-length assertions, back-references, quantifiers, and more - Srivastava, Anubhava (Packt Publishing, 2017)
Solve real world problems using Regex in Java. About This Book Discover regular expressions and how they work Implement regular expressions with Java to your code base Learn to use regular expressions in emails, URLs, paths, and IP addresses Who This Book Is For This book is for Java developers who would like to understand and use regular expressions. A basic knowledge of Java is assumed. What You Will Learn Understand the semantics, rules, and core concepts of writing Java code involving regular expressions Learn about the java.util. Regex package using the Pattern class, Matcher class, code snippets, and more Match and capture text in regex and use back-references to the captured groups Explore Regex using Java String methods and regex capabilities in the Java Scanner API Use zero-width assertions and lookarounds in regex Test and optimize a poorly performing regex and various other performance tips In Detail Regular expressions are a powerful tool in the programmer's toolbox and allow pattern matching. They are also used for manipulating text and data. This book will provide you with the know-how (and practical examples) to solve real-world problems using regex in Java. You will begin by discovering what regular expressions are and how they work with Java. This easy-to-follow guide is a great place from which to familiarize yourself with the core concepts of regular expressions and to master its implementation with the features of Java 9. You will learn how to match, extract, and transform text by matching specific words, characters, and patterns. You will learn when and where to apply the methods for finding patterns in digits, letters, Unicode characters, and string literals. Going forward, you will learn to use zero-length assertions and lookarounds, parsing the source code, and processing the log files. Finally, you will master tips, tricks, and best practices in regex with Java. Style and approach This book will take readers through this learning journey using simple, easy-to-understand, step-by-step instructions and hands-on examples at every stage.